The (Un)Productivity of American Colleges: From "Cost Disease" to Cost-Effectiveness - Goldrick-Rab, Sara; Harris, Douglas (My University, 2010)
We show that the productivity of American colleges and universities in terms of degree production is plummeting. This is partly due to rising costs that economists typically attribute to Baumol's well known "cost disease," but we demonstrate two other basic problems contributing to productivity declines. First, using cost-effectiveness analysis, we find that several popular programs and strategies in higher education are not cost-effective. Second, there is little rigorous evidence with which to judge the cost-effectiveness of most postsecondary programs, perhaps reflecting a larger absence of incentives to improve productivity. Rather than simply a "cost disease," we argue that the problem is more a "system disease" -- one that is partly curable.
Keywords: Accountability, Autonomy, and Politics; Finance and Economics; Access, Persistence, and Success